Associations between Relationship Status, Anxiety, Sexual Function, and Sexual Satisfaction in Lesbian, Gay, and Bisexual People. Issue 1 (2nd January 2023) - Arthur, Elizabeth; Flynn, Kathryn; Jeffery, Diana; Cusatis, Rachel
Abstract: Objectives: The purpose of this study was to describe associations between relationship status, anxiety, and sexual function and satisfaction in lesbian, gay, and bisexual (LGB) adults. Methods: Linear regression determined associations between sexual function, relationship characteristics and anxiety in 979 LGB participants. Results: Relationship status was not related to sexual interest in gay men. Partnered relationship status was associated with higher sexual satisfaction for gay men, lesbians, and bisexual women. Anxiety symptoms were negatively associated with sexual interest, satisfaction, and orgasm pleasure for gay men but not associated with sexual outcomes in lesbian women. Conclusion: Using a nationally representative sample of LGB adults, differences were found in factors related to sexual function and satisfaction by gender and sexual orientation.